Gold Price Surge: Peoples Investment Strategy in Economic Uncertainty - Kalsum, Ummy; Rosalia, Olyvia (Nomico, 2025)
This study aims to analyze community investment strategies in response to the surge in gold prices amid global economic uncertainty. Such uncertainty is characterized by high inflation, fluctuations in the rupiah exchange rate, and unstable international geopolitical conditions. Data were obtained through a survey of 130 respondents from various age groups and educational backgrounds in Indonesia. The research method used is quantitative, employing a descriptive approach and multiple linear regression analysis using SPSS. The findings indicate that the majority of the population chooses gold as their primary investment instrument due to its perception as a safe haven asset. Simultaneously, the variables of gold price, financial literacy, and economic risk perception have a significant influence on people's investment strategies. Among these three variables, gold price exerts the most dominant effect. Furthermore, financial literacy is found to play a crucial role in determining portfolio diversification, while risk perception is largely based on concerns about the economic future. These findings have important implications for policymakers in improving investor education and protection, especially in the digital era which increasingly facilitates access to both physical and digital gold investment instruments.